FAKTOR PROFITABILITAS, KEBIJAKAN HUTANG, KEBIJAKAN DIVIDEN, KEPUTUSAN INVESTASI DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN PERBANKAN - Ni Nyoman Ayu Suryandari; Anak Agung Putu Gede Bagus Arie Susandya; I Gede Wisnu Eka Wijaya (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Ngurah Rai, 2021)
Company value plays an important role in showing the prosperity of shareholders in the company. High company value indicates shareholder prosperity. This study aims to examine the effect of variable profitability, debt policy, dividend policy, investment decisions and firm size on firm value. The population in this study includes all banking companies listed on the Indonesia Stock Exchange for the 2018-2020 period as many as 46 banking companies. Determination of the sample using purposive sampling technique. The sample in this study were 12 banking companies with a total of 36 observations. The analytical technique used was multiple linear analysis. The results showed that the variables of profitability and investment decisions have a positive effect on firm value. Meanwhile, debt policy, dividend policy and firm size have no effect on firm value.